THE CONSTITUTIONAL JUDGE AND HIS DISCRETION (American Journal of Research in Humanities and Social Sciences, 2024)
The issue of the authority of the legislator and the constitutional judge is one of the topics that sparked widespread debate in constitutional circles. The principle is that the legislative authority does not interfere in judicial affairs. Here we mean negative interference, that is, interference that violates the basic principles stipulated in the Constitution, including the principle of judicial independence and separation of powers. The legislative authority exercises the most dangerous authority in the state. Because it sets laws that represent its will and that are binding on everyone, including the judicial and executive authorities, it carries out its duties as an institution whose mission is to legislate laws. The legislator is authorized by the constitution to enact legislation that ensures the proper performance of each authority’s function. However, this authorization must not violate the recognized constitutional rules.